2018
DOI: 10.1029/2017gl076457
|View full text |Cite
|
Sign up to set email alerts
|

Eddy Covariance Measurements of Methane Flux at a Tropical Peat Forest in Sarawak, Malaysian Borneo

Abstract: Tropical biogenic sources are a likely cause of the recent increase in global atmospheric methane concentration. To improve our understanding of tropical methane sources, we used the eddy covariance technique to measure CH 4 flux (F CH4 ) between a tropical peat forest ecosystem and the atmosphere in Malaysian Borneo over a 2-month period during the wet season. Mean daily F CH4 during the measurement period, on the order of 0.024 g C-CH 4 ·m À2 ·day À1 , was similar to eddy covariance F CH4 measurements from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
(56 reference statements)
3
17
1
2
Order By: Relevance
“…The corresponding CH 4 flux densities are higher than the CH 4 flux densities reported for the Lupar and Saribas Rivers but much lower than the flux densities from drainage canals in Central Kalimantan and Sumatra (Table 4). Our CH 4 flux densities are, however, 330 comparable to recently published CH 4 eddy covariance measurements (Tang et al, 2018) in the Maludam National Park, which is drained by the Maludam River, and measurements of the CH 4 release from peat soils when the water table is high and CH 4 from rice paddies (Couwenberg et al, 2010), see Table 4. The mean annual N 2 O and CH 4 emissions for the individual rivers were calculated by multiplying the mean flux density, F, for each river (Table 4) with the river surface area given in 335 Table 2.…”
Section: Emission Estimates 325supporting
confidence: 83%
“…The corresponding CH 4 flux densities are higher than the CH 4 flux densities reported for the Lupar and Saribas Rivers but much lower than the flux densities from drainage canals in Central Kalimantan and Sumatra (Table 4). Our CH 4 flux densities are, however, 330 comparable to recently published CH 4 eddy covariance measurements (Tang et al, 2018) in the Maludam National Park, which is drained by the Maludam River, and measurements of the CH 4 release from peat soils when the water table is high and CH 4 from rice paddies (Couwenberg et al, 2010), see Table 4. The mean annual N 2 O and CH 4 emissions for the individual rivers were calculated by multiplying the mean flux density, F, for each river (Table 4) with the river surface area given in 335 Table 2.…”
Section: Emission Estimates 325supporting
confidence: 83%
“…When the root zone is inundated, changes in biological processes in vegetation driven by solar energy input might be the most important factors controlling diurnal variation in measured NEE-CH 4 (Figure 5a-d), as reported in northern peatlands (Chanton, Whiting, Happell, & Gerard, 1993;Garnet, Megonigal, Litchfield, & Taylor, 2005;Kim et al, 1998;Long et al, 2010;Whiting & Chanton, 1996) and recently reported over tropical peatland (Tang et al, 2018) and flooded forest (Dalmagro et al, 2019). At the natural forest, the observed positive correlation between NEE-CH 4 and canopy conductance to water vapor suggests that CH 4 could be dissolved in the water, absorbed by the roots, transported with sap flow, and emitted through the stem by effervescence (Garnet et al, 2005;Nisbet et al, 2009).…”
Section: High Gwl Supports Diurnal Variability In Nee-chsupporting
confidence: 66%
“…Our annual NEE-CH 4 over the natural forest are in the same range as those measured using the eddy covariance technique above a tropical peatland in the presence of CH 4 -transporting trees (10.0-14.4 g m −2 year −1 ; Tang et al, 2018;Wong et al, 2018). In the absence of CH 4 -transporting trees, a study in a tropical peatland reported no significant diurnal pattern in NEE-CH 4 (Sakabe et al, 2018) and far lower annual CH 4 emissions (0.12-0.23 g m −2 year −1 ), despite similar GWLs to our forest site.…”
Section: Comparison Of Nee-ch 4 With Other Studiesmentioning
confidence: 60%
See 2 more Smart Citations